Sustainable cities and the convergence of knowledge. (1st January 2012) - Thorpe, Graham; ArziFard, Amirhossein; Kashuk, Sam
There is a convergence of knowledge between previously separate scholarly disciplines that is resulting in a transformation of how professionals and other workers organise and share knowledge. Increasing pressure to design and manage buildings and cities that are environmentally sustainable puts the onus on architectural, engineering and construction workers to share their expertise. Multiphysics software is becoming commercially available enabling building designers to investigate the interactions of a range of physical processes that affect building energy consumption. If this software is to be used creatively professionals within the architectural industries must have an increased awareness of physical principles. Parametric design software has also emerged as a tool that enables architects to explore a hitherto impossibly large number of alternative designs. These developments are having profound effects on the quotidian lives of professionals in the construction industries, and they raise important questions concerning their education and how knowledge must be embedded in society.